Legal Instruments to Improve the Protection of Human Rights - Rubio Correa, Marcial (1984)
There is a distinct step in the development of human rights in the sphere of international law and in the sphere of the domestic law of States, with a clear advantage for the former. This means, however, that human rights constitute declarations that, in many cases, cannot be realized due to the lack of domestic legal mechanisms to make them effective. The author proposes various alternatives to be considered both at the constitutional level and at the legislative and institutional levels of the States, with a view to finding ways of legally guaranteeing human rights, beyond Habeas Corpus and amparo actions. The proposals deal, fundamentally, with hermeneutic mechanisms of law, strengthening of the democratic system, and creation and development of institutions with exclusive competence in matters of protection and surveillance of the fulfillment of human rights.